Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Study on the stability of the excavation face in parallel overlapping shield tunnels - Geng Wang; Yuhang Lin; Zhaoping Li; Zhijun Ye; Rucun Han (Tunnelling and Underground Space Technology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Integrated physiological and metabolomic analysis reveals metabolite diversity and cultivar-specific characteristics during post-ripening in four Torreya grandis cultivars - Zhenmin Ma; Han Tao; Lin Li; Ruqi Meng; Jinwei Suo; Weiwu Yu; Yuanyuan Hu; Fei Gao; Mohamed A. Farag; Zuying Zhang; Jiasheng Wu; Lili Song (Postharvest Biology and Technology, 2025)

Grain size and geochemical evidence for the integration of the Yellow River through the Sanmen Gorge - Han Hu; Ziying Yu; Jiaxing Yang; Jiayi Lin; Wenjing Yang; Baofeng Li; Gang Hu; Xin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Relating small waterbody denitrification with ecosystem respiration in an intensive anthropogenic region - Xuemei Zhao; Yi Zhu; Xu Yang; Li Zhang; Xuan Huang; Chunwang Li; Kebing Chen; Han Lin; Dongli She; Yongqiu Xia (Journal of Hydrology, 2025)

Deciphering the acute toxicity mechanisms of PFAS in algae: A molecular descriptor and binding energy hierarchy perspective - Yanting Li; Lin Zhao; Lu Wang; Han Zhang; Guodong Xing; Jinrui Yuan; Yongkui Yang; Peizhe Sun (Journal of Hazardous Materials, 2025)

Confinement engineering of Co@C nanocages in 3D g-C3N4 scaffolds boosts photothermal CO2-to-fuel conversion - Yanan Wang; Jingjie Li; Rui Zhang; Tingting Xu; Chenlu Li; Jie Ma; Han Li; Liwei Lin; Song Xu; Man Zhou; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced photothermal combustion efficiency of propane in the presence of SO2 over Mo-doped Pt/WO3 catalyst: Rational utilization of Ptδ+-(SO4)δ- - Lijing Han; Huimin Chai; Jinliang Lin; Kaiting Chen; Qingwei Li; Qiuhong Zhou; Jun Ye; Hai Liu; Xinyu Han; Zeshu Zhang; Yibo Zhang (Journal of Environmental Chemical Engineering, 2025)

Hydrocarbon generation and pore evolution in marine organic-rich shales across maturation stages - Xueying Wang; Kun Zhang; Zhenxue Jiang; Yanhua Lin; Yan Song; Chengzao Jia; Shu Jiang; Lin Jiang; Hulin Niu; Jing Li; Yunbo Zhang; Xingmeng Wang; et al. (Fuel, 2025)

Dendrobium officinale polysaccharide inhibits M1 macrophage polarization via activating SENP1-SIRT3 signaling and alleviates ulcerative colitis - Jing Zhang; Xiaohe Lin; Huaying Song; Yumin Xie; Shaozhen Hou; Song Huang; Xianhua Du; Hailun Li; Yun Han; Jian Liang; Xiaoyan Jiang (Food Research International, 2025)

A “three-in-one” competitive immunosensor for colorimetric, fluorescence and photothermal triple-signal β-lactoglobulin monitoring in foods by quantum dots anchoring cerium based coordination polymer - Tianlin Wang; Meijun Lu; Qinqing Han; Xianqing Huang; Xiaodong Lin; Yan Ma; Lianjun Song; Tiange Li (Food Chemistry, 2025)

A systematic analysis of the sensory qualities of Asparagus cochinchinensis (lour.) Merr. From the four major production areas in China: Sensory characteristics, key flavor substances, and molecular mechanisms of flavor formation - Jingping Zhong; Shuyu Deng; Mengqi Li; Honglin Yin; Xinming Chen; Zhiyan Deng; Xiaoming Bao; Qingchu Tan; Junzhi Lin; Dingkun Zhang; Gang Shen; Li Han; et al. (Food Chemistry, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

Molecular characteristics of brown carbon aerosols over a forest atmosphere in the Qinling region of central China - Xin Zhang; Shuyan Xing; Jianjun Li; Rui Wang; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Environmental Pollution, 2025)

Synergistically promoting humification and polluting gas reduction in cherry tomato straw composting via carbon bioavailability management - Jiacong Lin; Guangyi Li; Dingmei Wang; Yuqi Pang; Zhuoya Han; Xingwei Meng; Liwen Mai; Shiliang Peng; Qinfen Li (Environmental Pollution, 2025)

Electrode interfacial wettability engineering for high-efficiency synthesis of dimethyl sebacate via Kolbe electrolysis - Linchuan Cong; Xinxin Li; Fuyu Han; Yupeng Wu; Kewen Ma; Ciduo Wang; Nan Lin; Haibo Lin (Chemical Engineering Journal, 2025)

CO2-mediated SEI engineering via Li2C2O4 pre-lithiation: A dual-functional strategy for high-stability SiOx/Gr anodes - Lifan Wang; Peng Han; Lin Zhang; Cong Zhong; Min Chen; Ruixiang Li; Yiheng Wu; Zhengping Zuo; Xindong Wang; Xuefeng Wang; Chun Zhan; Guicheng Liu (Chemical Engineering Journal, 2025)

Theranostic nanoplatform for triple-negative breast cancer therapy: Autophagy suppression-coordinated siRNA delivery triggers apoptosis, ferroptosis, and pyroptosis via photothermal activation - Guobao Ning; Lishen Yang; Bilian Li; Jianghua Lin; Shufen Li; Fengqi Zhou; Han Chen; Xingye Zheng; Weijie Sun; Hui Zhao; Can-Peng Li (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Morphological, histological and multi-omics analysis revealed the molecular response of female western mosquitofish (Gambusia affinis) to levonorgestrel exposure - Kaichun Chen; Tongfu Lu; Weijian Chen; Shengyue Lin; Dingxian Chen; Shuzheng Ye; Weiqian Liang; Sixun Li; Binhua Deng; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Gut Microbiota Improve the Prediction of Stroke-Associated Pneumonia Risk and Outcomes in Acute Ischemic Stroke - Yi-si Lin; Jia-hao Chen; Wei-hao Zhuang; Jia-ni Huang; Yi-han Chen; Jie Zhang; Jia Li; Meng Huang; Jia-long Hou; Shuang-jie Qian; Zhi-bo Chen; Yan-lei Zhang; et al. (Translational Stroke Research, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Strip clearcutting and replanting effects on soil organic carbon, microbial necromass carbon, and microbial carbon use efficiency in Chinese fir plantations - Xinran Zhao; Huiling Zhou; Hongwei Xu; Lin Xu; Chengming You; Li Zhang; Bo Tan; Zhenfeng Xu; Han Li; Lixia Wang; Sining Liu; Xinglei Cui; et al. (Plant and Soil, 2025)

Zinc Fertilizer Application in Different Stages Changes the Accumulation and Remobilization of Zinc in Winter Wheat - Muhammad Fraz Ali; Yuxi Niu; Guoming Li; Lijuan Ma; Xiang Lin; Shubo Gu; Yong Han; Dong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Enhanced production of eicosapentaenoic acid and fucoxanthin in Phaeodactylum tricornutum via a two-stage strategy with multifactorial synergistic effects - Xin Dong; Meng-Han Zhao; Chen-Xi Li; Xiao Lin; Ning Ma; Hong-Jin Qiao; Dian-Feng Han; Ying-Jiang Xu (Journal of Applied Phycology, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

RETRACTED ARTICLE: Exploring the potential of miR-9a-5p in circadian rhythm and cognitive recovery following brain injury in neonatal rats - Changqin Han; Lin Li; Yajing Yun; Chenxi Feng; Meifang Jin; Xin Ding; Bin Sun; Lixiao Xu (Functional & Integrative Genomics, 2025)

Can delivery riders act as informal guardians in crime prevention? - Shuli Zhou; Lin Liu; Han Yue; Kaiyin Yang; Jianjun Li; Guangwen Song (Applied Geography, 2025)

Levonorgestrel-induced sex reversal in mandarin fish (Siniperca chuatsi): An effective protocol for all-female production and its aquaculture applications - Shiyan Liu; Jinmeng Teng; Suhan Peng; Shuang Liu; Jiaqi Lin; Long Chen; Ju Hu; Haoran Lin; Caiyun Sun; Shuisheng Li; Songlin Chen; Chong Han; et al. (Animal Reproduction Science, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Feasibility study of the integration of buoyancy energy storage systems in floating offshore wind: A case study in Taiwan - Ting-Li Lin; Shun-Han Yang (Ocean Engineering, 2025)

Microalgal-bacterial granular sludge enhances oxytetracycline removal: Microbial responses, degradation pathways, and adaptive mechanisms - Yunqing Li; Xiaoying Zheng; Haidong He; Ruijie Hu; Zongshuo Han; Jiaqing Tao; Tao Lin; Wei Chen (Journal of Hazardous Materials, 2025)

Ecological restoration in plateau pika-disturbed alpine meadows: Soil-microbe-enzyme stoichiometry and microbial adaptations during vegetation recovery of bare patches - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Journal of Environmental Management, 2025)

Elucidation of the molecular mechanism for the phenolic acid removing the fishy odor bound to proteins in sea bass - Huanqing Lei; Yaoxing Chen; Rui Wang; Qiaohui Zeng; Langhong Wang; Jian Li; Wenhao Lin; Xinan Zeng; Zhong Han; Ji Ma; Ruoyong Wang (Food Chemistry, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Unraveling ozone formation sensitivity to ambient VOCs and NOx at urban and mountain sites in a typical city of eastern China - Xiaorong Zhang; Deming Han; Jiandong Shen; Feng Chen; Liuyan Cao; Jinhan Chen; Xu Lin; Yang Yang; Lin Yang; Wenjing Li; Xiaowei Qiao; Shuangxu Zhou; et al. (Environmental Pollution, 2025)

Mechanical and acoustic emission characteristics of anisotropic rock subjected to tiered cyclic intermediate principal stress - Kaihui Li; Guangzhen Du; Dongya Han; Zhen-Yu Yin; Jiangteng Li; Hang Lin (Engineering Geology, 2025)

Influence of prolonged exposure to acetamiprid on the toxicology of the decapod crustacean Pacific white shrimp Penaeus vannamei - Zhen-Fei Li; Zhi Luo; Zhi-Yu Lin; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Redefining cyclodextrin-based systems: A multiscale framework of structure, function and application interconnection - Yu-han Zhang; Yuting Lin; Yihan Lin; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Effects of plateau pika disturbance on soil net nitrogen mineralization from small to large scales in alpine meadows - Yuan Yuan Duan; Huan Yang; Jie Li; Ni Wang; Tong Wu; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (CATENA, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Atmospheric nitrogen deposition to cropland in Fujian province, China - Ziyin Yu; Mengjuan Han; Zhang Wen; Wenqing Li; Changzheng Wu; Xin Ma; Wen Xu; Ruotong Si; Xiaoping Xia; Aohan Tang; Lin Zhang; Goulding Keith; et al. (Atmospheric Environment, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Effects of Angelica sinensis polysaccharides on growth performance, antioxidant capacity, immune response, intestinal microbiota, and liver transcriptome in Mauremys mutica - Zike Yan; Jingu Shi; Kaijie Lin; Yuhan Li; Yutian Zhan; Mingzuo Gao; Hongyao Zhang; Shuyu Han; Jingzhen Liang (Aquaculture International, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Correction: Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

Molecular mechanisms and therapeutic application of pyrogallic acid in treating multidrug-resistant Klebsiella pneumoniae infections in American bullfrogs (Aquarana catesbeiana) - Han Lin; Furong Li; Yufang Huang; Yongping Ye; Ziyan Chen; Chun Liu; Ruiai Chen (Aquaculture, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Preparation of sludge derived fuels for co-incineration in waste incinerators: Industrial tests and life cycle assessment - Yanfei Lin; Hanqiao Liu; Guoxia Wei; Tong Li; Qianlong Han; Zilu Liu; Xinrui Su; Yifan Chen (Sustainable Production and Consumption, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

PDHA1-mediated H3K18 lactylation is involved in arsenic-induced nonalcoholic fatty liver disease by activating the CD36–NLRP3 inflammasome axis - Han Li; Zhenyang Li; Lin Chen; Xiaoshan Peng; Dapeng Wang; Qian Sun; Yuting Chen; Aihua Zhang; Qizhan Liu; Huanwen Tang (Journal of Hazardous Materials, 2025)

Airborne human-associated ARGs in municipal wastewater treatment plants - Ying Wang; Yunping Han; Lin Li; Jianwei Liu; Hongyu Tian (Journal of Hazardous Materials, 2025)

The potential of Cupriavidus sp. DF5525 degrading high concentrations of p-dichlorobenzene - Hong-Lin Ma; Ze-Shen Liu; Qun Han; Yi Yang; De-Feng Li (Journal of Hazardous Materials, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Contrasting effects of different acid rain types on soil nitrogen pools - Xingyu Pan; Yi Jian; Zhenfeng Xu; Bo Tan; Xinglei Cui; Tong Zhang; Lin Xu; Han Li; Li Zhang; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Algal-bacterial granular sludge cultured with different inoculum: The discrepancy of granulation mechanism and greenhouse gas emissions - Xiongcheng Deng; Xiaoying Zheng; Zongshuo Han; Jiaqing Tao; Yunqing Li; Tianxing Hu; Yi Fan; Tao Lin (Journal of Environmental Chemical Engineering, 2025)

Microstructure-property relationships in Cu/N-TiO₂ photocatalytic concrete for marine applications: Role of preparation strategies - Guoliang Lin; Mengchen Huang; Sen Chen; Kun Li; Kun Han; Minyi Liu; Yuxiang Li; Wenhua Chen (Journal of Environmental Chemical Engineering, 2025)

Synthesis, characterization, and in vitro hypolipidemic mechanisms of sugar-SA triazole conjugates as potent pancreatic lipase inhibitors - Ruge Cao; Jingxin Li; Yue Sun; Yichen Li; Xiao-Lin Zhang; Han Ding; Xue-Wei Liu (Food Chemistry, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Single-electrode multiplex sensing via metal ion displacement method - Yiming Zhang; Zhi Chen; Songrui Wei; Huiling Lin; Yujun Zhang; Yingxia Liu; Jing Wang; Qi Gao; Defa Li; Han Zhang; Zhongjian Xie (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Cobalt-functionalized sulfur-deficient MoS2: Unlocking enhanced Fenton-like activity via phase transformation and Co sites regeneration - Cunxin Lin; Na Wang; Sixun Li; Han Li; Jie Yang; Ziqiu Ren; Yunchen Du; Qun Xu (Chemical Engineering Journal, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Tartaric acid-functionalized MOF-808 with tailored ultramicroporous for efficient separation of C2H2 from C2H2/C2H4/CO2 mixture - Chen-Ning Li; Liu Lin; Daqiang Yuan; Zheng-Bo Han (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Target mitochondrial pyroptosis with sequential delivery of nanoliposomes to alleviate secondary injury following traumatic brain injury - Yuwei Lin; Jiaqi Jin; Qingyi Han; Diancheng Hang; Zijun Chen; Suihan Ye; Qing Guo; Xuyang Huang; Jinna Li; Hengzhu Zhang; Xuefeng Zhang; Yufu Zhu (Chemical Engineering Journal, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Unlocking the synergistic effects in biomass-plastic Co-pyrolysis using a hybrid machine learning approach with blended rule descriptors - Peng Jiang; Wenjie She; Hao Zhang; Lin Li; Han Lin; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Biomass and Bioenergy, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Levonorgestrel-induced anal fin masculinization in mosquitofish: Do TGF-β/BMP signaling and osteogenic remodeling underpin endocrine disruption in aquatic ecosystem? - Weiqian Liang; Tongfu Lu; Dingxian Chen; Weijian Chen; Kaifeng Wang; Jie Lai; Shengyue Lin; Lin Gui; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Engineering a recombinant VP2-Based neutralizing epitope vaccine candidate against canine parvovirus: a preliminary immunogenicity assessment - Qing Wu; Yuhan Jin; Weiyue Cao; Zeheng Ren; Xinyu Li; Zhitong Li; Jiachi Han; Chunxu Shi; Rui Gao; Min Yan; Shengrui Zhu; Wenpeng Guan; et al. (Veterinary Research Communications, 2025)

Deformation and Seepage Characteristics of Gassy Coal Subjected to Cyclic Loading–Unloading of Pore Pressure - Shugang Li; Chongzhi Wang; Bin Zhou; Haiqing Shuang; Haifei Lin; Shoujian Peng; Biao Hu; Han Yang; Hang Liu (Natural Resources Research, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

Dietary isoleucine requirement of grass carp (Ctenopharyngodon idella) based on growth performance, muscle nutritional value, and extracellular matrix gene expression - Kaixuan Ren; Lin Feng; Pei Wu; Yang Liu; Dong Han; Wenbing Zhang; Ling Tang; Shuwei Li; Shengyao Kuang; Xiaoqiu Zhou; Weidan Jiang (Aquaculture, 2025)

Dietary purines and health: Metabolism, impact, and regulation - Yuan Song; Qiang Li; Jianfeng Lu; Mengying Ren; Qingli Han; Zhicheng Cai; Hong Wang; Lin Lin; Bin Zheng; Changhu Xue (Trends in Food Science & Technology, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Olfactory dysfunction induced by pesticides: Adverse outcomes, emerging mechanisms, and risk for neurodegenerative diseases - Lin Wang; Si-Yang Liu; Han-Yue Zheng; Shou-Min Fang; Li Zhuo; Feng Xu; Quan-You Yu (Pesticide Biochemistry and Physiology, 2025)

A grid search-based optimal trajectory planning approach for automatic berthing of underactuated unmanned surface vehicles - Shidi Wu; Shifeng Ding; Lin Geng; Zihan Chen; Sen Han; Li Zhou (Ocean Engineering, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Identification of heavy metal transport-related genes and microRNAs in response to cadmium toxicity and micronutrient deficiency in barley roots - Liuhui Kuang; Jian Chen; Jie Ding; Tao Yan; Fei Gao; Lin Li; Zhigang Han; Dezhi Wu (Journal of Hazardous Materials, 2025)

In-situ construction of BiOBr/UiO-66(Zr/Ce) S-scheme heterojunction for efficient selective photocatalytic CO2 reduction to CO - Mengting Shen; Ling Wang; Man Zhou; Liwei Lin; Han Li; Yanan Wang; Song Xu; Zhongyu Li (Fuel, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Reactivation mechanism of loess-mudstone historical landslide under rainfall-vibration effects - Haoyu Dong; Jiading Wang; Lin Li; Dengfei Zhang; Zailiang Xu; Kai Han; Shan Li; Lirong Qi (Engineering Geology, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Multifunctional Cu-engineered NH2-MIL-125Ti@ZnIn2S4 heterojunction with dual-channel H2O2 activation for ultrafast water-mediated Cr(VI) photoreduction - Guangyuan Chen; Wei Han; Chenyang Lin; Yubao Li; Shijian Zhou; Yan Kong (Chemical Engineering Journal, 2025)

Unraveling the role of phosphorus on V2O5-WO3-CeO2/TiO2 catalysts: Mechanisms for enhanced NH3-SCR and water resistance - Hongbo Qi; Jianwen Lai; Qiong Yuan; Yunfeng Ma; Yichao Qian; Zhongkang Han; Xiaoqing Lin; Xiaodong Li (Chemical Engineering Journal, 2025)

Multi-level resource utilization of food-grade nanomaterials from brewing residues: Synergistic polyphenol-pullulan membranes for litchi preservation - Congyu Lin; Peiqi Lu; Peihang Li; Zhimin Zhang; Jingqiu Ma; Yunfei Hou; Xiao Han; Zhongwei Ji; Zhilei Zhou; Dawei Li; Jian Mao (Chemical Engineering Journal, 2025)

Creating easily accessible adsorption sites in natural wood-derived hierarchical porous carbon via a controlled delignification strategy for organic pollutant removal - Minjiao Chen; Meihua Li; Peng Jiang; Wenjie She; Han Lin; Jiahua Zhu (Biomass and Bioenergy, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

Halomonas sp. NEC-1, an ectoine-rich and wide pH tolerant halophilic bacterium isolated from a salt lake of Xizang, China - Yingchao Ma; Zhongshi Sun; Tashilhamo; Yukang Li; Hanying Zou; Yuanliang Zhao; Feiyang Lin; Xuekai Han; Liying Sui; Chi Zhang (Journal of Oceanology and Limnology, 2025)

Berberine attenuates the expression of NLRP3 and downstream inflammasome effectors in diabetic retinopathy - Na Li; Ji-Lin Chen; Yi-Jian Sun; Jia-Fan Sun; Ting-Hua Wang; Amy Yi Hsan Saik; Alan Han-Kiat Ong (Journal of Natural Medicines, 2025)

Canopy Exchange Process of Heavy Metals in Subtropical Urban Forest in Southern China - Han-Wen Zhang; Zhi-Yun Jiang; Yi-Hua Xiao; Lin Huang; Shui-Xia Li; Zhi-Gao Fu; Si-Yi Zhang; Yu-Jun Ma (Environmental Processes, 2025)

Succession of biological soil crusts modifies patterns of soil eukaryotic communities along a precipitation gradient - Lin Xu; Yongping Kou; Xiangzhen Li; Chaonan Li; Jiabao Li; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengmin You; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2025)

PINN and KAN temperature prediction of carbon Fiber/Epoxy composite materials irradiated by nuclear environment simulated intense heat fluxes - Xiaoxiang Han; Jun Li; Lin Yuan; Xin Zhang; Weijie Zhu; Yang Liu; Haiyang Zhang; Boyu Wang (Annals of Nuclear Energy, 2025)

Overview of Non-Destructive Exploration Technologies for Complex Urban Underground Spaces - Jiu-lin Li; Han-ming Zhang; Tian-cai Li; Fang-ning Li; Yong-hui Li; Jian-ning Wang (Applied Geophysics, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Estimation of surface duct parameters using AIS data based on Bayesian inversion method - Hong-Guang Wang; Li-Jun Zhang; Jie Han; Li-Feng Huang; Qing-Lin Zhu (Frontiers in Marine Science, 2025)
Automatic Identification System (AIS) operates within a very high frequency (VHF) maritime mobile band, which could be impacted by surface duct seriously. Utilizing AIS signals for atmospheric duct inversion is a relatively new technique in passive remote sensing. This study employs the Bayesian method to conduct inversion of maritime surface ducts based on AIS signals, categorizing surface ducts into surface-based and elevated-surface ducts. Initially, preliminary data on surface-based duct and elevated-surface duct parameters are acquired from historical sounding data, followed by correlation analysis and probability density distribution fitting of these surface duct parameters. Subsequently, the inversion method steps are provided, and using the same measured AIS data, the likelihood function and posterior probability are calculated by directly employing historical samples and samples generated using Latin Hypercube Sampling (LHS), to accomplish the estimation of surface duct parameters. Directly utilizing historical samples and LHS-generated samples for Bayesian inversion can consistently and accurately yield results with an elevated-surface duct, with the latter being slightly more accurate than the former. The root mean square errors for the AIS path loss, calculated using the inverted elevated-surface duct parameters, are 5.9 dB and 4.4 dB when compared with the measured data. In contrast, the error calculated from the inverted surface-based duct parameters is 21.9 dB.

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Lipid profiling of Toxoplasma tachyzoites and the mouse host - Lijun Shi; Lin Liang; Wenchao Li; Cun Liu; Kun Han; Xinghui Zhao; Zhanzhong Zhao (Veterinary Parasitology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Microbiological mechanisms of lignin- and humus-derived small molecule addition promoting straw conversion into soil organic matter in a sodic soil - Jingwang LI; Lin CHEN; Fengxia YUE; Congzhi ZHANG; Donghao MA; Guixiang ZHOU; Jiangli WANG; Changdong HAN; Biao FENG; Jiabao ZHANG (Pedosphere, 2025)

Harmonizing stakeholder interests in urban renewal: A novel planning approach using explainable machine learning and spatial optimization - Chuan Lin; Yilun Liu; Zhongyou Yuan; Hongmei Wang; Guang Li; Zegen Zhou; Han Wang; Xinyue An (Land Use Policy, 2025)

Heavy metal pollution enhances herbivore resistance of male poplars over females through modifying volatile-mediated tritrophic interactions - Tiantian Lin; Xiaotao Han; Guoqing Zhu; Wanci He; Lianghua Chen; Jing Li; Yan Wang; Tao Li (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Life cycle assessment of scaled-up pyrite-based solid-state batteries for energy storage applications - Md Rashed Hossain; Muyue Han; Lin Li (Journal of Cleaner Production, 2025)

Revealing the characteristics and nitrogen metabolism mechanism of Anammox biofilm assisted by nanoscale zero-valent iron - Zongshuo Han; Xiaoying Zheng; Zhilin Zhao; Wenfei Li; Haidong He; Yi Fan; Tao Lin (Journal of Environmental Management, 2025)

Enhanced low-temperature simultaneous removal of nitrogen oxides and polychlorinated dibenzodioxins and dibenzofurans over vanadium-cerium-tungsten oxide supported on titanium dioxide catalyst: A pilot-scale evaluation - Jianwen Lai; Hongbo Qi; Yunfeng Ma; Xiaoqing Lin; Zhongkang Han; Heidelore Fiedler; Xiaodong Li (Journal of Environmental Chemical Engineering, 2025)

SiO2 particles induce pulmonary fibrosis by modulating NLRP3 through the ROS/Keap1/Nrf2 signaling pathway in rats - Shuang Li; Wei-Lei Gong; Lin Liu; Bo Shao; Shun-Li Jiang; Huan Li; Ye Song; Gui-Zhi Han; Zhao-Qiang Zhang (Food and Chemical Toxicology, 2025)

Galnt3, an enzyme engaged in protein glycosylation modification, is essential for the maintaining of intestinal health in zebrafish - Jing Gao; Wenjin Li; Jingyuan Lin; Yilin Han; Guangdong Ji; Zhenhui Liu (Fish & Shellfish Immunology, 2025)

Cobalt-modification on UiO-bpydc MOF facilitates ligand-to-metal charge transfer for superior visible-light photocatalytic degradation of refractory fluoroquinolone antibiotics - Kaichun Lin; Jingjun Qin; Zhang Liu; Weicheng Xu; Meng Li; Yuanzhi Zheng; Wei Han; Guangying Zhou; Jianzhang Fang; Zhanqiang Fang; Feng Peng; King Lun Yeung (Environmental Research, 2025)

Ecological risks under combined pollution: Toxicological effects of clothianidin and microplastics on Penaeus vannamei - Zhi Luo; Zhi-Yu Lin; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Aquatic Toxicology, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Exploring the role of the rhizosphere in soil carbon cycling: impacts on pools and components of SOC along a chronosequence of Cryptomeria japonica plantations in subtropical China - Dengjie Zhou; Yaling Yuan; Jing Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Li Zhang; Hongwei Xu; Lixia Wang; Sining Liu; et al. (Plant and Soil, 2025)

Seasonal dynamics of ammonia-oxidizing archaea and bacteria in subalpine forests of western Sichuan - Li Zhang; Su Chen; Zebin Jiao; Sining Liu; Wenlan Huang; Lulu Huang; Liyun Yu; Lixia Wang; Bo Tan; Hongwei Xu; Lin Xu; Chengming You; et al. (Plant and Soil, 2025)

Organic amendments with low C/N ratios enhanced the deposition of crop root exudates into stable soil organic carbon in a sodic soil - Jingwang Li; Lin Chen; Congzhi Zhang; Changdong Han; Biao Feng; Donghao Ma; Guixiang Zhou; Jiabao Zhang (Plant and Soil, 2025)

Simulation of the optical performance of a single corner cube retroreflector for the TianQin Project and lunar laser ranging stations - Zhizhao He; Hui Li; Xida Han; Xudong Lin; Xianlin Wu; Hongxiao Zhang; Ming Li (Advances in Space Research, 2025)

Astrocyte involvement in brain metastasis: from biological mechanisms to therapeutic strategies - Teng Zhou; Yuxin Yan; Mingxi Lin; Cheng Zeng; Xinhui Mao; Yifei Zhu; Jinlu Han; Dou-Dou Li; Jian Zhang (Cancer and Metastasis Reviews, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Enhancing growth, pigment composition, polysaccharides, fatty and amino acid content in Ulva prolifera by manipulating temperature, light intensity, and photoperiod - Xuan Zhou; Mingzi Lin; Jianan Jiang; Shenyuan Liang; Han Xu; Wenrong Zhu; Nianjun Xu; Yahe Li (Aquaculture, 2025)

Metformin alleviates cadmium-induced reproductive toxicity by enhancing mitochondrial biosynthesis and epigenetic modifications in female mice - Jiaqiao Zhu; Min Zhu; Hangbin Zhao; Yifan Lin; Xiaoxue Han; Ankai Tan; Yixian Wang; Yonggang Ma; Junwei Li; Zongping Liu (Toxicology and Applied Pharmacology, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Dynamic responses of soil microbial communities to long-term co-contamination with PBAT and cadmium - Zhouchang Zhang; Yiqiong Zhang; Yufan Wang; Jiao Feng; Tengqi Xu; Siqi Han; Jiaxi Liu; Tianjiao Song; Li Li; Yanbing Lin (Journal of Hazardous Materials, 2025)

Characteristics, immobilization of linoleic acid isomerase from Bifidobacterium breve and its application in rice bran oil - Lin Li; Ning Wang; Liqi Wang; Fuming Yang; Weining Wang; Yike Han; Dianyu Yu (Food Research International, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Antiviral activity of epicatechin against Singapore grouper iridovirus in vitro and in vivo - Lin Huang; Jihui Kuang; Jieying Yu; Qing Yu; Weiqiang Xu; Mingzhu Liu; Yunyi Wei; Shuyu Han; Yanhua Huang; Pengfei Li (Fish & Shellfish Immunology, 2025)

MCPA-Na exposure in aquatic systems: disruption of pathways and increased susceptibility to infection in fish - Yanxia Lin; Ran Shi; Mengzhen Wang; Yali Wang; Yunfan Han; Yongcui Ma; Liyin Li; Xiaohua Xia (Aquatic Toxicology, 2025)

Cycleift: A deep transfer learning model based on informer with cycle fine-tuning for water quality prediction - Yang Yu; Shixin Zhao; Lintong Han; Lin Peng; Yanmei Xu; Qiujin Tian; Sen Chen; Zuogang Yang; Qiude Li; Zuquan Hu (Stochastic Environmental Research and Risk Assessment, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Review on the Molecular Characterization of Atmospheric Organic Aerosols Using High-Resolution Orbitrap Mass Spectrometry: Techniques, Applications, and Perspectives - Yue Lin; Xin Zhang; Lijuan Li; Zhiyu Li; Rui Wang; Shuyan Xing; Yuemei Han (Aerosol Science and Engineering, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

New insights into the impact of microplastics on nitrogen transformation in urban rivers based on field experiments - Cheng Yang; Yuanyuan Feng; Jinjiang Duan; Nayin Li; Qingping Zou; Peng Lin; Mengli Chen; Jiang Li; Han Zhang (Journal of Environmental Chemical Engineering, 2025)

Pilot-scale application on Fe-C coupled natural zeolite for total nitrogen removal in low C/N black odorous water - Hongyang Yu; Qiheng Han; Tao Li; Shanshan Lin (Journal of Environmental Chemical Engineering, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Fracture characteristics and fatigue failure signals of thermal storage rock under stepwise pulsation pressurization - Zhanming Shi; Jiangteng Li; P.G. Ranjith; Hang Lin; Taoying Liu; Kaihui Li; Dongya Han (Engineering Geology, 2025)

Freestanding vanadium oxides/carbon hybrid cathode with long-term cyclability at low current density for flexible aqueous zinc ion batteries - Zhouyang Qin; Gaoxu Han; Yilin Yang; Shengle Hao; Lingxiao Yu; Yuxiao Lin; Yunsong Li; Ruitao Lv; Wanci Shen; Feiyu Kang; Zheng-Hong Huang (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

The heterogeneous response in leaf traits among seasons and plant types of an evergreen broadleaf forest in western China to nitrogen addition was regulated by fertilization intensity - Wenzheng Chang; Qiu Song; Tianxing Liang; Jie Chen; Lixia Wang; Han Li; Li Zhang; Chengming You; Hongwei Xu; Lin Xu; Bo Tan; Zhenfeng Xu; et al. (Plant and Soil, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Exploring biosynthetic potential of the endophytic Penicillium turbatum BLH34 using whole-genome sequence analysis and molecular networking - Xuejun Wang; Jun Chen; Han Lin; Changli Min; Li Zhang; Zhimou Gao (Natural Product Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Newly isolated bacterium and arbuscular mycorrhizal fungus effectively reduce the root cadmium concentration and increase the root biomass of Ophiopogon japonicus - Lin Lin; Jin Li; Obey Kudakwashe Zveushe; Ying Han; Hengxing Zhang; Yu Qin; Victor Resco de Dios; Lei Zhou; Xiangyu Xi; Wei Zhang; Yulian Zhao; Amal Mohamed Omer; et al. (Journal of Hazardous Materials, 2025)

Polystyrene microplastics attenuated the impact of perfluorobutanoic acid on Chlorella sorokiniana: Hetero-aggregation, bioavailability, physiology, and transcriptomics - Zhilin Zhao; Xiaoying Zheng; Yue Li; Zongshuo Han; Yu Tang; Tianxing Hu; Tao Lin (Journal of Hazardous Materials, 2025)

Disparities in residential PM2.5 and disease burden across urban and peri-urban: A 2018–2019 multicenter on-site survey in China - Lin Fan; Wenying Zhang; Xiaotong Zhang; Hang Du; Weiyi Zhang; Li Li; Xu Han; Chao Wang; Wenhao Wang; Xianliang Wang (Journal of Environmental Management, 2025)

Soil nutrients determine multidimensional absorptive root traits of Cryptomeria japonica var. sinensis plantations along a chronosequence in subtropical forest - Chunran Liu; Lihua Wang; Jing Li; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Lin Xu; Hongwei Xu; Li Zhang; Lixia Wang; et al. (Journal of Environmental Management, 2025)

Fractal characteristics and acoustic early warning index of rock with thermal storage potential under fatigue fracturing - Zhanming Shi; Jiangteng Li; P.G. Ranjith; Mengxiang Wang; Hang Lin; Dongya Han; Kaihui Li; Taoying Liu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Characterization and risk-quantification of antibiotic resistome in grain-based and non-grain cropping soils - Jingpeng Li; Lin Zhu; Xiaodi Li; Xuezhu Han; Jiaming Yi; Ying Wu; Meizhen Wang (Environmental Pollution, 2025)

Seismic performance of grouted CFDST column base: Investigation and design method - Zhi-Cheng Yang; Wei Li; Yu-Feng Cheng; Lin-Hai Han (Engineering Structures, 2025)

Core-shell structured magnetic beads based on sodium alginate/chitosan for nitrogen removal enhancement - Han Zhang; Bolin Li; Cong Ding; Rui Ni; Xiangyu Lin (Chemical Engineering Journal, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

When crop straw meets CO2-intensive process industries in China: The potential of CO2 mitigation and techno-economic analysis - Minjiao Chen; Peng Jiang; Meihua Li; Guanhan Zhao; Han Lin; Liwen Mu; Lee Chung Lau; Jiahua Zhu (Biomass and Bioenergy, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Immune dysregulation of decidual NK cells mediated by GRIM19 downregulation contributes to the occurrence of recurrent pregnancy loss - Ying Wang; Anliang Guo; Lin Yang; Xiaojuan Han; Qianni Li; Jin Liu; Yilong Han; Yang Yang; Lan Chao (Molecular and Cellular Biochemistry, 2025)

Spatial adaptations in hospitality amid COVID-19: A case study of Xiamen's B&B sector - Juan Lin; Han Li; Shuyu Xing; Weiye Xiao (Applied Geography, 2025)

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

Dynamic brain responses and systemic regulatory mechanisms in yellow catfish (Pelteobagrus fulvidraco) exposed to acute hypoxia - Man Wang; Shasha Zhao; Jie Wang; Li Li; Ruru Lin; Dong Han; Xiaoming Zhu; Lei Zhang (Aquaculture, 2025)

Aerosol particles released from grit chambers of nine urban wastewater treatment plants in typical regions: Fugitive characteristics, quantitative drivers, and generation process - Wenwen Wang; Kaixiong Yang; Lin Li; Yunping Han (Water Research, 2025)

Patterns and drivers of soil autotrophic nitrification and associated N2O emissions - Shumin Guo; Roland Bol; Zhutao Li; Jie Wu; Haiyan Lin; Xiaomeng Bo; Zhiwei Zhang; Zhaoqiang Han; Jinyang Wang; Jianwen Zou (Soil Biology and Biochemistry, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Dynamic response of vegetation to meteorological drought and driving mechanisms in Mongolian Plateau - Shenghang Gao; Shengzhi Huang; Vijay P. Singh; Xiaoya Deng; Limin Duan; Guoyong Leng; Wenwen Guo; Yifei Li; Lin Zhang; Zhiming Han; Qiang Huang (Journal of Hydrology, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Exploring dialkyl carbonate as a low-carbon fuel for combustion engines: an overview - Guofeng Yang; Qingxuan Wang; Lincheng Li; Delin Lyu; He Lin; Dong Han (Fuel, 2025)

WTAP-mediated m6A modification of Hmgb2 contributes to spermatogenic damage induced by PM2.5 exposure - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Chaofeng Shi; Tong Wang; Lei Sun; Lin Ao; Fei Han; Qing Chen; Jia Cao; Jinyi Liu (Environmental Pollution, 2025)

Developing a digital twin for dam safety management - Shao-Lin Ding; Jia-Jun Pan; Yanli Wang; Han Xu; Dian-Qing Li; Xin Liu (Computers and Geotechnics, 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

Development of a Mixotrophic Strategy for Efficient Cultivation of a Coccolithophore, Chrysotila roscoffensis - Luyao Zhang; Zhichao He; Yan Sun; Jian Li; Pengfei Cheng; Nicolas Spiros Agathos; Chengxu Zhou; Lin Zhang; Jichang Han (Journal of Ocean University of China, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Bimetallic Pt–Ni0.5 nanoparticles with enhanced oxidase like activity for Hg2+ detection in water - Han Wu; Sayed Haidar Abbas Raza; Mengyao Wang; Zhongqi Lin; Duan Jiang; Zhenlin Xu; Hongtao Lei; Xiangmei Li (Analytica Chimica Acta, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Effects of hypoxic stress on liver metabolism, oxidative stress, and immunity in yellow catfish (Pelteobagrus fulvidraco) at different water temperatures - Jie Wang; Chuankun Zhu; Man Wang; Li Li; Ruru Lin; Dong Han; Xiaoming Zhu; Lei Zhang (Aquaculture, 2025)

Enhanced virulence of Acinetobacter johnsonii at low temperatures induces acute immune response and systemic infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Jingyang Sun; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Veterinary Microbiology, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

CLANN: Cloud amount neural network for estimating 3D cloud from geostationary satellite imager - Han Lin; Jun Li; Min Min; Feng Zhang; Keyue Wang; Qunyong Wu (Remote Sensing of Environment, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Enhancing hexavalent chromium stable reduction via sodium alginate encapsulation of newly isolated fungal and bacterial consortia - Obey Kudakwashe Zveushe; Jackson Nkoh Nkoh; Víctor Resco de Dios; Tendai Terence Manjoro; Fidèle Suanon; Hengxing Zhang; Wenfang Chen; Lin Lin; Lei Zhou; Wei Zhang; Frank Sesu; Jin Li; et al. (Journal of Hazardous Materials, 2025)

Soil phosphorus dynamics and its correlation with ectomycorrhizal fungi following forest conversion in subtropical conifer (Picea asperata) forests - Lixia Wang; Shiyu Song; Huichao Li; Yang Liu; Lin Xu; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; Zhenfeng Xu; Li Zhang; et al. (European Journal of Soil Biology, 2025)

Analytical behaviour of concrete-encased concrete-filled steel tubular (CFST) member under combined compression and shear load - Zhi-Cheng Yang; Lin-Hai Han; Wei Li (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Fatigue fracture and energy evolution characteristics of sandstone under water–ice phase transitions via the discrete element method - Zhidan Zheng; Zhanming Shi; Mengxiang Wang; Hang Lin; Jiangteng Li; Dongya Han; Kaihui Li; Chong Jiang (Computers and Geotechnics, 2025)

Combined exposure effects: Multilevel impact analysis of cycloxaprid and microplastics on Penaeus vannamei - Zhi-Yu Lin; Zhi Luo; Zhen-Fei Li; Zhen-Qiang Fu; Feng-Lu Han; Er-Chao Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Soft yet powerful: Nano-coatings preserve transfer film integrity - Xiaoyi Wu; Xin Han; Lin Zhang; Mengyu Li; Guoxin Xie (Chemical Engineering Journal, 2025)

Synthesis and antitumor activity of ultra-low molecular weight hyaluronic acid-decorated camptothecin conjugates - Changsheng Chen; Henan Zhang; Jingjun Han; Lin Yang; Shuang Li; Qingwen Jia; Junqiang Fang; Peixue Ling; Shuaishuai Wang (Carbohydrate Polymers, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Intersecting sustainability and governance: The impact of industrial land price distortion on carbon emission efficiency in China - Zhiji Huang; Han Li; Mingyue Song; Lin Ma (Applied Geography, 2025)

TUFT1 Modulates Cell Proliferation, Migration, Invasion, Stemness and EGFR Signaling in Cervical Cancer through Interacting with and Targeting ATF1 - Chunhua Han; Huifen Gao; Fengqiong Li; Lin Lin; Muying Qian; Lin Feng (Cell Biochemistry and Biophysics, 2025)

Preliminary Study on the Structure of Fungal Communities in Artificial Reef Areas in the Northern Yellow Sea - Jiamin Yan; Yue Yue; Shengkai Lin; Hanshitong Gu; Ziyi Han; Qingxia Li; Tao Tian; Xu Wei; Zhongxin Wu (Oceans, 2025)
The construction of artificial reefs is the primary ecological project of marine ranching and one of the most important methods of creating habitats for marine organisms. To date, studies on artificial reefs have taken a macroscopic perspective, with few studies having investigated the fungal communities in artificial reefs in the North Yellow Sea. Therefore, the aim of this study was to determine the distribution patterns of seawater quality, sediment properties, and fungal communities following the placement of artificial reefs of different materials in the North Yellow Sea. A sampling survey of marine ranching in the northern Yellow Sea was conducted in August 2023. Sediment and seawater samples were collected from the stone and concrete artificial reef areas as well as from the areas without constructed reefs as a control. Research shows that the total phosphorus (TP), total nitrogen (TN), and total organic carbon (TOC) concentrations were higher in the concrete reef than that in the other two regions. We obtained 735 fungal operational taxonomic units (OTUs) which were assigned to 11 phyla and 374 genera. Significant differences in the beta-diversity of the fungal communities were found among the three sampling regions, and the dominant species varied in seawater and sediment samples from different reef areas. Ascomycota was the most abundant phylum in the seawater and sediment samples, followed by Basidiomycota. pH and dissolved oxygen (DO) emerged as the most important factors affecting fungal communities in the seawater samples, whereas mean grain size, TN, and TOC had a significant effect on the communities in the sediments, with TP and TOC playing the most critical roles. Our study compared the characteristics of fungal communities in seawater and sediments in distinct types of artificial reefs and control areas, revealing the main environmental factors affecting fungal communities, which is of great significance for protecting biodiversity and evaluating the ecological effects of artificial reef placement.

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Impact of defatted black soldier fly (Hermetia illucens) larvae meal on health, muscle texture, and intestinal microbiota in Pacific white shrimp (Penaeus vannamei) - Tong Chang; Hongxing Lin; Fenglu Han; Chang Xu; Erchao Li (Aquaculture, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Optimization of the life cycle environmental impact of shell powder and slag concrete using response surface methodology - Yi Han; Bo Yang; Li-Yi Meng; Hyeong-Kyu Cho; Runsheng Lin; Xiao-Yong Wang (Process Safety and Environmental Protection, 2025)

Exosomal miRNA reprogramming in pyroptotic macrophage drives silica-induced fibroblast-to-myofibroblast transition and pulmonary fibrosis - Lin Zhang; Jiaqi Tian; Ning Li; Yongheng Wang; Yulan Jin; Hongying Bian; Min Xiong; Zitong Zhang; Jiahua Meng; Zhengpu Han; Shuyin Duan (Journal of Hazardous Materials, 2025)

Degradation of anthracene and phenanthrene by strain Streptomyces sp. M-1 and its application in the treatment of PAHs-contaminated water - Zaimei Zhang; Hui Li; Han Han; Lijian Qin; Wei Lu; Lin Yue; Zongzhen Guo; Shengsong Gao; Shuang Chen; Huie Liu; Dong Wang; Jiqian Wang (Journal of Environmental Management, 2025)

Non-additive effects of leaf-litter flammability on eight subtropical tree species: Implications for forest species composition and fire susceptibility - Pujie Wei; Li Tang; Zixuan Xiong; Byron B. Lamont; Lin Chen; Weixing Xue; Zeyao Zhao; Wenxiong Lu; Jisi Han; Wanwan He; Wei Yang; Zhaogui Yan (Journal of Environmental Management, 2025)

Efficient photoelectrocatalytic degradation of tetracycline coupled with hydrogen production by N-doped carbon layer-wrapped TiO2 nanorods - Yan Li; Lili Yu; Jiayang Xie; Zilong Han; Haotong Chen; Zhiyuan Zhang; Zehao Lin; Li Li (Journal of Environmental Chemical Engineering, 2025)

Half-day (daytime and nighttime) precipitation extremes in China: Changes and attribution from 1981 to 2022 - Jiahao Han; Shibo Fang; Xiaomao Lin; Zhanhao Zhang; Man Li; Yanru Yu; Wen Zhuo; Xinyu Wang (Global and Planetary Change, 2025)

A kinetic study of CO2 and H2O addition on NO formation for ammonia-methanol combustion - Yuzheng Gao; Youping Li; Xianting Wei; Yang Zheng; Shixuan Yang; Qirong Yang; Han Jiang; Yiran Zhang; He Lin (Fuel, 2025)

American ginseng fruit: Antioxidant capacity, bioactive components, and biosynthesis mechanism during development - Yujuan Zhang; Lijuan Hou; Jing Hu; Xianchang Wang; Shujing Guo; Hongqing Xie; Yun Zhou; Wen Ai; Lin Li; Xin Wang; Li Ren; Fangzhou Zhao; et al. (Food Research International, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Non-destructive detection of freshness in crayfish (Procambarus clarkii) based on near-infrared spectroscopy combined with deep learning - Qing-li Han; Jian-feng Lu; Jiao-jiao Zhu; Lin Lin; Zhi Zheng; Shao-tong Jiang (Food Control, 2025)

MEHP induced mitochondrial damage by promoting ROS production in CIK cells, leading to apoptosis, autophagy, cell cycle arrest - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

DTD1 modulates synaptic efficacy by maintaining D-serine and D-aspartate homeostasis - Xiao Liu; Chaojuan Yang; Zhuoran Lin; Jianing Li; Bin Yin; Xuepei Lei; Wei Han; Boqin Qiang; Pengcheng Shu; Chen Zhang; Xiaozhong Peng (Science China Life Sciences, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

A bottom-up nationwide analysis of sectoral land use reveals spatial heterogeneity across the United States - Zhixiu Han; Wei Xie; Yiru Song; Lin Sun; Huajun Yu; Bin Chen; Yang Li; Yutao Wang (Resources, Conservation and Recycling, 2025)

Corrigendum to “Meliasanines A–L, tirucallane-type triterpenoids from Melia toosendan with anti-inflammatory properties via NF-κB signaling pathway” [Phytochemistry 225 (2024) 114192]> - Li-Li Shao; Kai-Qin Lin; Han-Fei Liu; Zhi-Yao Li; Ni Zhang; Chao Chen; Wei-Dong Pan; Hua-Yong Lou; Jin-Yu Li (Phytochemistry, 2025)

Occurrence characteristics, removal efficiencies and potential health risks of typical viruses in rural domestic sewage: A review - Yingming Zhu; Su Xu; Yu Zhou; Xuesong Guo; Yunping Han; Jun Zhan; Lin Li; Junxin Liu (Journal of Water Process Engineering, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

The mango bacterial black spot altered the endophyte community structure and diversity - Meng-Jiao Li; Ji-Han Li; Wen-Lin Li; Yuan He; Yu-Bo Ma; Xin-Yu Li; Yan Wang; Cai-Xia Li; Xin-Rong Ma (International Journal of Food Microbiology, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Study on the pathways of thermochemical sulfate reduction between sulfates and alkanes at low temperatures - Yiya Wang; Liqiang Zhang; Chuantao Zhu; Riyi Lin; Xinlu Han; Kunlun Xie; Ruiqi Liu; Jinyu Li; Chenxing Huang; Qiwei Dong; Xinwei Wang (Fuel, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

In-situ forming flame-retardant gel polymer electrolyte through Ritter reaction: An innovative strategy for enhancing the safety of lithium metal battery - Si-Xin Jia; Tian-Qi Xiang; Zi-Han Zhang; Jian-Jun Zhou; Lin Li (Chemical Engineering Journal, 2025)

B, N dual-doped porous carbon nanoframeworks as bifunctional peroxymonosulfate activators for ultrafast adsorption and decomposition of microcontaminants in water - Han Li; Na Wang; Cunxin Lin; Ziqiu Ren; Yunchen Du; Qun Xu (Chemical Engineering Journal, 2025)

Preparation of a novel organic-inorganic composite sludge bioflocculant (SBF) from dewatered sludge as raw material: Characteristics, flocculation mechanism and application for domestic sewage - Jingyun Ge; Hongyu Tian; Lin Li; Yunping Han; Jianwei Liu (Bioresource Technology, 2025)

Responses of surface ozone under the tropical cyclone circulations: Case studies from Fujian Province, China - Keyue Wang; Rui Zhao; Qunyong Wu; Jun Li; Hong Wang; Han Lin (Atmospheric Pollution Research, 2025)

Supplementation with probiotics co-cultivation improves the reproductive performance in a sow-piglet model by mother-infant microbiota transmission and placental mTOR signaling - Suchen Li; Tingting Lu; Zhixin Lin; Yuanyuan Zhang; Xinchen Zhou; Meng Li; Hui Miao; Zhiren Yang; Xinyan Han (World Journal of Microbiology and Biotechnology, 2025)

Metagenomic Analysis of Gut Microbiome of Persistent Pulmonary Hypertension of the Newborn - Linli Han; Chuyang Lin; Yue Lan; Yimin Hua; Jinlin Wu; Zhenxin Fan; Yifei Li (Cardiovascular Toxicology, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.